A case of ALK-rearranged lung adenocarcinoma associated with syndrome of inappropriate antidiuretic hormone. (2020) - Miyashita, Yoshihiro; Hanawa, Kotaro; Kobayashi, Hiroaki; Kumagai, Takashi; Inomata, Kie; Tsutsui, Toshiharu; Kakizaki, Yumiko; Oyama, Toshio
Abstract: A 60-year-old man with a history of smoking was transferred to our hospital for consciousness disorder. A diagnosis of ALK- rearranged lung adenocarcinoma associated with a paraneoplastic electrolytic disorder was made following a cutaneous needle biopsy. Both the primary lung lesion and multiple metastases shrunk and his electrolytic disorder resolved after the introduction of a first-line molecular-targeted drug chemotherapy with crizotinib. We herein report a case of ALK -rearranged lung adenocarcinoma accompanied by SIADH, successfully treated with crizotinib.